(untitled) (Swiss Medical Weekly, 2019)
The treatment of human diseases using gene-editing technology has been envisioned for several decades with the realisation that so many were associated with mutations in DNA. The Human Genome Project opened new doors for identifying the genetic bases for human suffering. Research on gene editing has been active since the 1970s, but the technology has seen substantial growth and application just within the past decade. Simply stated, CRISPR technology has become a phenomenon in both biomedical and therapeutics research. Concurrently, cell therapies and pluripotent stem cell research have also been refined and now interfaced with CRISPR technology to enhance and maximise their potential in modelling as well as treatment of human diseases. In this review, we discuss the novel and revolutionary modality of gene editing, as this marks a new era in research and medicine. We also discuss gene-modifying technologies leading to CRISPR, as they are still being used for a wide variety of genomic applications. The modes and challenges for delivery of gene editing components are also discussed. Lastly, we review examples of human diseases that are not only amenable to gene editing techniques, but also show true promise of cure in the early 21st century of genetic correction and gene repair.